Perception of Acupuncture Compared with Biomedicine among Health Practitioners - Rastiti, Ida Ayu Anom; Strisanti, Ida Ayu Suptika; Ariani, Ni Komang Sri (Global Medical & Health Communication (GMHC), 2023)
Compared with biomedicine held by medical experts, perspectives on acupuncture may impact how the general populace uses acupuncture. Therefore, research on the opinions of medical professionals regarding acupuncture therapy is crucial. This cross-sectional study was conducted from July to September 2022 using a questionnaire. The study participants are doctors and nurses from three clinics in Bali province who had at least one year of working experience and were willing to be research respondents. Descriptive analysis and multiple logistic regression are used to determine the participants' perceptions and predictors of their perception. Of 155 participants, the majority (64%) have a positive perception of acupuncture compared with biomedicine. Participants with prior acupuncture usage were 9.01 times more likely than those without previous acupuncture use to have positive perceptions of acupuncture compared to biomedicine (Adj OR=9.01; 95% CI; p=0.001). The results of this study show that acupuncture is seen positively by health practitioners as an effective modality, has few side effects, and is supported by science. Health practitioners' perceptions are affected by their prior acupuncture experience. It is crucial to understand how medical professionals feel about acupuncture. Medical professionals' opinion impacts every patient's decision to seek therapy because one of their duties as specialists is to offer patients clinical judgment, information, and suggestions.